PROXIMATE, MINERAL, AND VITAMIN ANALYSIS OF Dioscorea bulbifera - Okoh, Emmanuel Chidera (International Journal of Allied Sciences (IJAS), 2025)
This study investigated the proximate, mineral, and vitamin composition of Dioscorea bulbifera, a tuber known for its nutritional and medicinal properties. The Dioscorea bulbifera bulbils used in this study were purchased from Eke Market in Agbani, Nkanu West Local Government Area, Enugu State. The moisture, crude protein, ash, crude fat, and fiber contents were determined using stipulated methods. The results of the proximate analysis revealed a high moisture content (64%), which is greater than the carbohydrate level (29.03%), while carbohydrates are higher than crude protein, ash, crude fiber, and crude fat (1.1%, 1.5%, 0.69%, and 0.64% respectively). The mineral analysis showed elevated concentrations of magnesium (Mg), calcium (Ca), potassium (K), phosphorus (P), and sodium (Na) with values of 79.63 mg/g, 37.92 mg/g, 6.81ppm, 5.2mg/g, and 0.53ppm respectively, reflecting the tuber's potential to contribute to essential mineral intake. Furthermore, the vitamin analysis indicated significant levels of vitamins A-B carotene (106.28mg/100g), B6 (116.12mg/100g), C/ascorbic acid (28.3mg/100g), riboflavin (13.18mg/100g), and B12 (2.81mg/100g). These findings underscore the importance of Dioscorea bulbifera as a rich source of nutrients with potential health benefits, such as improved energy levels, bone health, and antioxidant activity. This study highlights the nutritional significance of Dioscorea bulbifera and its potential application in addressing micronutrient deficiencies.